High tumor CD161 expression predicts a survival advantage and marks a Th1-skewed microenvironment - Burns, Briana Amicarella; Chandra, Manasvi; Konduri, Vanaja; Decker, William K. (Frontiers in Immunology, 2025)
CD8+CD161+ T-cells exhibit augmented memory and cytolytic properties, mediating enhanced immunity in murine tumor models and improved survival in human non-small cell lung cancer. This T-cell subset might serve as a biomarker of positive response to therapy or even be isolated to augment current immunotherapeutic approaches yet limited knowledge of CD161 expression in human cancers restricts practical application. Here we bioinformatically tested the hypothesis that CD161 expression may be associated with positive outcomes in human cancers and investigated mechanisms underlying any observed advantages. Using TCGA-PANCAN dataset, we analyzed expression of CD161 in over 10,000 human tumors, correlating expression levels with survival. CD161 expression was highly correlated and largely co-expressed with CD8, indicating that observed benefits could be attributed to CD8+CD161+ T-cells. While patients with high CD161 expression exhibited a clear survival advantage over those with low expression, this survival advantage was highly dependent on co-expression of CD11c, indicating a reliance on dendritic cells (DC). To further explore the mechanism by which high CD161 expression confers a survival advantage in cancer, we analyzed available scRNA-sequencing data derived from 31 melanoma tumors. Tumors exhibiting high CD8+CD161+ infiltration also exhibited greater expression of cDC1 and TH1 transcription factors along with higher levels of inflammatory cytokine transcripts. CD8+CD161+ cells themselves displayed enhanced cytotoxicity markers and reduced exhaustion markers compared to CD8+CD161neg T-cells. The data suggest that CD161 could serve as a biomarker for positive outcomes and that DC play a critical in vivo role in the propagation of CD161+ T-cell responses.